Penguatan Sistem Pengendalian Internal Pengelolaan Keuangan Sekolah dalam Upaya Membangun Budaya Akuntabilitas di Lingkungan Madrasah Aliyah Negeri - Widya Rizki Eka Putri; Einde Evana; Retno Yuni Nur Susilowati; Rona Majidah; Rialdi Azhar (Jurnal Pengabdian Masyarakat, 2026)
This community service activity aims to strengthen the internal control system (ICS) in financial management at MAN 2 Bandar Lampung to foster a culture of accountability and support the development of an Integrity Zone (IZ) toward a Corruption-Free Area (WBK). The main problems faced by the partner include the absence of formal ICS and financial SOP documents, weak internal supervision, and low literacy in public accountability. Through participatory training and technical assistance, the program facilitated the preparation of ICS documents, financial Standard Operating Procedures (SOPs), and internal monitoring and evaluation (M&E) instruments based on the COSO framework and Ministry of Religious Affairs regulations. The results show a 32% improvement in participants’ understanding of internal control, accountability, and segregation of duties. Furthermore, the partner successfully developed official ICS and SOP documents and drafted M&E instruments ready for implementation. This activity demonstrates that strengthening ICS through training and mentoring effectively enhances institutional capacity and human resources in realizing transparent, accountable, and sustainable financial governance as a foundation for establishing an Integrity Zone in the education sector.